Intravascular Lithotripsy for Treatment of Severely Calcified Mesenteric Stenosis - Mohammad Saud Khan, MD (JACC: Case Reports, 2020)
Intravascular lithotripsy (IVL) is an emerging approach for modification of calcified atherosclerotic plaque. We report 2 cases of IVL used for calcific mesenteric stenosis, one in de novo superior mesenteric artery stenosis and another in celiac artery in-stent restenosis. In both cases, IVL was used successfully, reducing stenosis without any complications. (Level of Difficulty: Intermediate.)